Phylogeography of hepatitis B virus : the role of Portugal in the early dissemination of HBV worldwide - Marcelino, Rute; Ezeonwumelu, Ifeanyi Jude; Janeiro, André; Mimoso, Paula; Matos, Sónia; Briz, Veronica; Pimentel, Victor; Pingarilho, Marta; Marinho, Rui Tato; Marcelino, José Maria; Taveira, Nuno; Abecasis, Ana (PLoS, 2022)
In Portugal, the genetic diversity, origin of HBV and the Portuguese role in the dissemination of HBV worldwide were never investigated. In this work, we studied the epidemic history and transmission dynamics of HBV genotypes that are endemic in Portugal. HBV pol gene was sequenced from 130 patients followed in Lisbon. HBV genotype A was the most prevalent (n = 54, 41.5%), followed by D (n = 44, 33.8%), and E (n = 32, 24.6%). Spatio-temporal evolutionary dynamics was reconstructed in BEAST using a Bayesian Markov Chain Monte Carlo method, with a GTR nucleotide substitution model, an uncorrelated lognormal relaxed molecular clock model, a Bayesian skyline plot, and a continuous diffusion model. HBV subgenotype D4 was the first to be introduced in Portugal around 1857 (HPD 95% 1699–1931) followed by D3 and A2 a few decades later. HBV genotype E and subgenotype A1 were introduced in Portugal later, almost simultaneously. Our results indicate a very important role of Portugal in the exportation of subgenotypes D4 and A2 to Brazil and Cape Verde, respectively, in the beginning of the XX century. This work clarifies the epidemiological history of HBV in Portugal and provides new insights in the early and global epidemic history of this virus.
Keywords: Phylogeography; hepatitis B virus; Portugal; dissemination